A novel storage and extraction method using solid-phase adsorption and ultrasonic-assisted nebulization extraction coupled to solid phase extraction. Issue 33 (14th August 2017) - Zhang, Peixu; Li, Xuwen; Cui, Li; Chen, Jiafeng; Qu, Yan; Wang, Xiaozhong; Wu, Qian; Liu, Ying; Zhou, Chunkui; Jin, Yongri
Abstract : A novel storage and extraction method was developed for biofluids. Abstract : A novel storage and extraction method was developed for biofluids. Plasma spiked with four types of minor ginsenosides (Rg2, Rg3, Rh1 and Rh2 ) was used as a model biofluid to evaluate this method. The method was based on solid-phase adsorption and ultrasonic-assisted nebulization coupled with solid phase extraction (SPA-UANE-SPE). Diatomaceous earth was used as an adsorbent to store the plasma for long periods of time at room temperature. Ultrasonic-assisted nebulization system-solid phase extraction was used to extract the four minor ginsenosides from the plasma. Some experimental parameters, such as the type and amount of the adsorbent, the ultrasonic-assisted nebulization extraction time, the pH of the extraction solution, the concentration of ZnSO4, the amount of C18, and the type and volume of the eluent were investigated and optimized. Under the optimized conditions, the recoveries of four minor ginsenosides were in the range of 78.5–91.4%, and the RSDs are in the range of 3.5–4.4%. For the storage stability test, the stability of the method was better than that of 4 °C storage and was similar to that of −20 °C storage. Compared with other methods, the proposed method had a better extraction performance and was advantageous in terms of ease of operation, stable long term storage, and minimal requirements for storage conditions. Thus, this method may be effective for sample preparation in biofluid analysis.